Canine Leishmaniasis in Brazil: Serological Follow-Up of a Dog Population in an Endemic Area of American Visceral Leishmaniasis - Alba Valéria Machado da Silva; Adelzon Assis de Paula; Daniela de Pita Pereira; Reginaldo Peçanha Brazil; João Carlos Araujo Carreira (Journal of Parasitology Research)
We performed a serological, clinical, and parasitological follow-up of a dog population in an endemic area of American Visceral Leishmaniasis estimated by indirect immunofluorescent assay (IFA) and western blot (WB). After twelve months, the results obtained from IFA demonstrated that 50% were seropositive and two serological profiles were observed: the first one ranging from 1/40 to 1/80 and the second ≥1/160. By WB, it was observed that the same percentage and sera from positive dogs presented the recognition of the peptides of 29 and 32 kDa up to 8 months before IFA serum conversion. Among the positive dogs, all the sera from symptomatic ones with tissue parasitism recognized the peptide of 68.5 kDa. Our results suggest the need of modifications in the control measures regarding the elimination of the dogs. They also corroborate the high sensitivity and specificity of western blot in the diagnosis of canine leishmaniasis, suggesting the possibility of its association with IFA.